VALUES AND PSYCHOLOGICAL WELLBEING OF YOUTH: A SUSTAINABLE INTERCONNECTION - Mayurakshee Gangopadhyay (UIN Sunan Gunung Djati Bandung, 2021)
Values play the most influential role in the well-being of individuals with a particular focus on youth and their development. Psychological well-being refers to how people evaluate their lives. The purpose of this study was to determine the impact of values on the psychological well-being of adolescents. Using a quantitative research method, a sample of 300 adolescents aged 18 to 21 years was selected. The Personal Values Questionnaire by Sherry and Verma, the Psychological Well-Being Scale by Sisodia and Choudhary and the General Information Schedule were provided to them. The results showed that the dimensions of personal values have a significant positive correlation with the dimensions of adolescent psychological well-being. All dimensions of psychological well-being are shown to be positively predicted by values.